MORPHOLOGICAL CHANGES IN THE MUSCULOSKELETAL SYSTEM IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS - Yarashova Shakhlo Ikrom qizi (Modern American Journals, 2025)
We studied the morphological features of musculoskeletal lesions associated with juvenile idiopathic arthritis (JIA) in 36 children. We determined the nature of histological changes in the synovial membrane, articular cartilage, and subchondral bone depending on the clinical form of the disease and the duration of the inflammatory process.
Keywords: Juvenile idiopathic arthritis, children, morphology, inflammation